Relating to rock art in the contemporary world: navigating symbolism, meaning and significance - Brady, Liam M., editor; Taçon, Paul S. C., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
Rock art is considered an archaeological artifact reflecting activities from the past, it is also a phenomenon with present-day meaning and relevance to both indigenous and non-indigenous communities. Challenging traditional ways of thinking about this recognizable form of visual heritage and providing insight into its contemporary significance.--Provided by publisher.
The place of rock art in the contemporary world / Paul S.C. Taçon and Liam M. Brady -- A fabricated past?: The case of Nyero Rock art site, Kumi District, Uganda / Catherine Namono -- "What rock art?" Stories from Northeast Thailand / Noel Hidalgo Tan, Atthasit Sukkham, Gemma Boyle, Watinee Tanompolkrang, Jutinach Bowonsachoti, and Duangpond Singhaseni -- What the places teach us: challenges for cultural tourism and indigenous stewardship of rock art sites in the North American midcontinent / John Norder and Dagmara Zawadzka -- "That painting now is telling us something": negotiating and apprehending contemporary meaning in Yanyuwa rock art, Northern Australia / Liam M. Brady and John J. Bradley -- Parks, petroglyphs, fish, and Zuni: an emotional geography of contemporary human-animal-water relationships / Kurt E. Dongoske and Kelley Hays-Gilpin -- Rock art in South African society today / Benjamin W. Smith -- Inscribing history: the complex geographies of Bedouin tribal symbols in the Negev Desert, Southern Israel / Davida Eisenberg-Degen, George H. Nash and Joshua Schmidt -- Land/people relationships and the future of rock art in the Laura Basin, Northeastern Australia / Noelene Cole -- From science to heritage: new challenges for world heritage rock art sites in Mediterranean Spain in the 21st century / Ines Domingo and Manuel Bea -- Rock art, cultural change, the media and national heritage identity in the 21st century / Paul S. C. Taçon -- Teaching and learning about rock art in Argentina / Dánae Fiore, Marianna Ocampo and Agustín Acevedo -- Recent art history in rock country: bark painters inspired by rock paintings / Luke Taylor -- Marks and meeting grounds / Ursula K. Frederick -- Establishing new ground: reflexive/reflective thinking and plotting a future for studying rock art in contemporary contexts / Liam M. Brady and Paul S.C. Taçon.
Keywords: Indigenous art; Rock paintings